Lack of Consensus Among Stroke Experts on the Optimal Management of Patients With Acute Tandem Occlusion. Issue 5 (May 2019) - Jacquin, Gregory; Poppe, Alexandre Y.; Labrie, Marilyn; Daneault, Nicole; Deschaintre, Yan; Gioia, Laura C.; Odier, Celine; Raymond, Jean; Roy, Daniel; Weill, Alain; Stapf, Christian
Abstract : Background and Purpose—: In patients with acute stroke caused by tandem occlusion, the benefit of immediate revascularization (stenting) of the cervical internal carotid artery lesion during endovascular thrombectomy is uncertain. We sought to determine current practice patterns and whether consensus existed among physicians with stroke expertise. Methods—: We distributed an online survey to stroke experts affiliated with the Canadian Stroke Consortium, the Canadian Interventional Neuro Group, the Society of Vascular and Interventional Neurology, and international ESCAPE trial (Endovascular Treatment for Small Core and Anterior Circulation Proximal Occlusion With Emphasis on Minimizing CT to Recanalization Times) collaborators. Questions were based on clinical scenarios, and multiple choice responses across a Likert-type scale were provided. The survey was sent out in September 2017. After 2 months, data were extracted and then analyzed using descriptive statistics. Results—: Responses from 162 stroke experts were analyzed; most were stroke physicians (n=65, 40.1%) and neurointerventionalists (n=74, 45.7%), from Canada (n=95, 58.6%), the United States (n=42, 25.9%), and other countries (n=25, 15.4%). Over half (n=96, 59.3%) of respondents consider acute stenting of the cervical internal carotid artery as a treatment option, whereas 40.7% (n=66) would never use it. Most respondents (n=113, 69.8%) agree that there exists uncertainty about the optimal acute management of patients with tandem occlusion. A majority (n=88, 54.3%) of physicians surveyed would include patients in a randomized trial addressing this question. Conclusions—: This survey shows high variability in practice about acute management of tandem occlusion. The existence of community equipoise underscores the importance of a randomized trial evaluating the benefit of acute internal carotid artery stenting in patients with tandem occlusion undergoing endovascular thrombectomy. Abstract : Supplemental Digital Content is available in the text.